Phospholipids: Pulling Back the Actin Curtain for Granule Delivery to the Immune Synapse - Gawden-Bone, Christian M.; Griffiths, Gillian M. (Frontiers in Immunology, 2019)
Phospholipids; including phosphoinositides, phosphatidylserine and phosphatidic acid, are important components of the inner leaflet of the plasma membrane. Modification of the lipid head groups by enzymes that add or remove phosphates, or in the case of phosphoinositides remove the sugar group, change the biophysical properties of the membrane. Phospholipids act as second messengers that, together with diacylglycerol, regulate a diverse range of signalling events converting extracellular changes into cellular responses, allowing adaption of cell behaviour to the local environment. Local changes in phospholipid distributions and membrane charge on the inner leaflet of the plasma membrane play important roles in immune cell function. Here we discuss the distribution and role of lipids and lipid regulators at the synapse to highlighting the importance of gross membrane changes on cytoskeletal arrangement at the T cell membrane and discuss discoveries that highlight similarities between the immunological synapse and the cilium.